1996
DOI: 10.1093/sleep/19.6.491
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Adjustable Versus Fixed NCPAP Treatment of Obstructive Sleep Apnea

Abstract: An automated positive airway pressure device that monitors respiratory patterns and provides dynamic, real-time, relational pressure has been developed for the treatment of obstructive sleep apnea (OSA). The purpose of this study was to compare self-adjusting pressure to classical nasal continuous positive airway pressure (NCPAP). Subjects were newly diagnosed patients with a minimum respiratory disturbance index (RDI) of 15 episodes per hour who had undergone NCPAP titration and been using classical NCPAP at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 0 publications
2
22
0
4
Order By: Relevance
“…A further cause of the relatively poor results with fixed CPAP in these studies may be that the AHI of the manual titration night, with longer periods of ineffective fixed nCPAP, was compared with the results of automatic CPAP. SCHARF et al [27], using a study design similar to that in the present study, also found a lower AHI with fixed CPAP compared to automatic CPAP (the Horizon), although the results of the two treatment modalities did not differ significantly.…”
Section: Discussionsupporting
confidence: 71%
“…A further cause of the relatively poor results with fixed CPAP in these studies may be that the AHI of the manual titration night, with longer periods of ineffective fixed nCPAP, was compared with the results of automatic CPAP. SCHARF et al [27], using a study design similar to that in the present study, also found a lower AHI with fixed CPAP compared to automatic CPAP (the Horizon), although the results of the two treatment modalities did not differ significantly.…”
Section: Discussionsupporting
confidence: 71%
“…There was no significant difference in sleep architecture measures for eight of nine studies. In one study (27), there was a significantly higher stage 3 and 4 sleep for the group who received APAP. There was no significant difference in arousal index scores in 11 studies (15-23,25,26,28) or for sleep time in three studies (18,25,26).…”
Section: Treatmentmentioning
confidence: 93%
“…In 12 studies (15)(16)(17)(18)(19)(20)(21)(22)(23)(26)(27)(28), there was no significant difference in AHI values, with scores for APAP being lower in four of the studies. In the other two studies (24,25), values for APAP were significantly higher than those for CPAP.…”
Section: Treatmentmentioning
confidence: 94%
“…However, despite differences in pressure output the effects on polysomnographic variables prove to be similar for most A-CPAP devices. All of the published reports demonstrate effectiveness in reducing, and usually normalising, obstructive respiratory disorders and sleep fragmentation [11,[33][34][35][37][38][39][40][41][42][43][44][45][46][47]. Although in some reports significant differences were found, they were small in absolute terms.…”
Section: Do Different A-cpap Devices Perform Equally?mentioning
confidence: 99%